Sales Promotion Girls' Sales Strategy Towards the Heborist Brand at I Gusti Ngurah Rai Airport - Dewi, Maulidiyah Pitaloka Kumala; RS, Aditya Manggala; Puriati, Ni Made (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study aims to determine the sales strategies implemented by Sales Promotion Girls (SPGs) for the Herborist brand in the International Departure (IDP) area of I Gusti Ngurah Rai Airport. This study uses a qualitative approach with observation, interview, and documentation methods. Informants in this study consisted of SPGs, supervisors, and several consumers who purchased Herborist products. The results of the study indicate that the sales strategies implemented by SPGs include a persuasive communication approach to consumers, product demonstrations, providing information about product benefits, and providing promotions or special offers to tourists. This strategy is considered effective in attracting consumer interest, especially tourists interested in natural Indonesian body care products. In addition, communication skills, product knowledge, and the appearance of SPGs are important factors in increasing consumer purchasing decisions. This study concludes that the sales strategies implemented by SPGs have an important role in increasing sales of Herborist products in the airport area. Therefore, the company needs to continue to improve training and development of SPG capabilities so that sales strategies can run more optimally.